Life Gets Even More Beautiful, During Extended 90 + Minutes - Engin Kocakarın (Türk Spor ve Egzersiz Dergisi)
In the 2022 Qatar World Cup, FIFA increased additional time by adding every moment when the ball isn’t played to the play time as an allowance for time lost. This also increased the number of goals scored during additional time. This research studies the impact of goals scored during additional time on match results caused by this extension in the second half of matches in Turkish Male Football Super League. Quantitative and qualitative methods were used. 250 matches played on weeks 1st–30th of 2022–2023 season of Turkish Spor Toto Male Football Super League were analyzed with document analysis, a qualitative research method. The matches, results, additional time, and goals scored during additional time were recorded. Then matches were separated into two equal-numbered groups including before and after the 2022 Qatar World Cup. The 125 matches on weeks 1st–14th and the 125 matches on weeks 14th–30th were analyzed for the number of total goals, total additional time, and the number of total goals scored during additional time with causal-comparative research model as a quantitative research method. In this research, Frequencies Analysis chosen from statistical analyses, Paired Sample t-Test and Pearson Correlation Analysis were used. According to the results, especially after the 2022 Qatar World Cup, the matches aren’t only ninety minutes for footballers any more. The matches may approach two hours with extended additional time. As a conclusion of this research, teams can be suggested to consider this situation and properly organize training plans and programs.